IMPLEMENTATION OF THE NORTH SUMATRA GOVERNOR REGULATION NUMBER 43 OF 2018 ON GENDER MAINSTREAMING (A DESCRIPTIVE STUDY AT GBKP PRIVATE SENIOR HIGH SCHOOL, KABANJAHE, KARO REGENCY) - Br Tarigan, Helenta; Jamaluddin, Yanhar; Batubara, Beby Masitho (International Journal of Cultural and Social Science, 2026)
Gender Mainstreaming (GM) is a strategy for achieving gender equality by integrating gender perspectives into public policies, including education. North Sumatra Province enacted Governor Regulation Number 43 of 2018 to guide GM implementation at the regional level. This study analyzes the implementation of this regulation at GBKP Private Senior High School in Kabanjahe, Karo Regency, and identifies the challenges faced. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation from key informants including the principal, vice principals, teachers, staff, and students. Data analysis followed the Miles and Huberman model. Findings show that GM implementation at the school is underway but not fully effective. Challenges include limited budget, lack of specialized training, and insufficient sustainable programs. While communication efforts have been made, they have not fully enhanced understanding of gender equality. Additionally, a strong patriarchal culture and absence of structured mechanisms hinder comprehensive implementation.